Downregulated PDIA3P1 lncRNA Impairs Trophoblast Phenotype by Regulating Snail and SFRP1 in PE - Zhengzheng Ding; Liuxin Wu; Yue Sun; Yuanyuan Zhu; Qing Zuo; Li Yuan; Cong Wang; Lizhou Sun; Yetao Xu; Yuanyuan Zhang (Analytical Cellular Pathology)
Preeclampsia (PE) manifests as a pregnancy-specific complication arising from compromised placentation characterized by inadequate trophoblast invasion. A growing body of evidence underscores the pivotal involvement of pseudogenes, a subset of long noncoding RNAs, in the pathological processes of PE. This study presents a novel finding, demonstrating a significant downregulation of the pseudogene PDIA3P1 in PE placental tissues compared to normal tissues. In vitro functional assays revealed that suppressing PDIA3P1 hindered trophoblast proliferation, invasion, and migration, concurrently upregulating the expression of secreted frizzled-related protein 1 (SFRP1). Further exploration of the regulatory role of PDIA3P1 in PE, utilizing human trophoblasts, established that PDIA3P1 exerts its function by binding to HuR, thereby enhancing the stability of Snail expression in trophoblasts. Overall, our findings suggest a crucial role for PDIA3P1 in regulating trophoblast properties and contributing to the pathogenesis of PE, offering potential targets for prognosis and therapeutic intervention.